Genetic Analysis of the Herpes Simplex Virus Type 1 UL20 Protein Domains Involved in Cytoplasmic Virion Envelopment and Virus-Induced Cell Fusion - Melancon, Jeffrey M. (American Society for Microbiology, 2004)
The herpes simplex virus type 1 UL20 protein (UL20p) is an important determinant for cytoplasmic virion morphogenesis and virus-induced cell fusion. To delineate the functional domains of the UL20 protein, we generated a panel of single and multiple (cluster) alanine substitutions as well as UL20p carboxyl-terminal truncations. The UL20 mutant genes could be broadly categorized into four main groups: Group I UL20 mutant genes complemented for both virus production and virus-induced cell fusion; Group II UL20 mutant genes did not complement for either virus-induced cell fusion or infectious virus production; Group III UL20 mutant genes complemented for virus-induced cell fusion to variable extents but exhibited substantially decreased ability to complement UL20-null infectious virus production; Group IV mutant genes complemented for infectious virus production but had variable effects on virus-induced cell fusion; this group included two mutants that efficiently complemented for gBsyn3, but not for gKsyn1, virus-induced cell fusion. In addition, certain recombinant viruses with mutations in either the amino or carboxyl termini of UL20p produced partially syncytial plaques on Vero cells in the absence of any other virally encoded syncytial mutations. These studies indicated that the amino and carboxyl termini of UL20p contained domains that functioned both in infectious virus production and virus-induced cell fusion. Moreover, the data suggested that the UL20p's role in virus-induced cell fusion can be functionally separated from its role in cytoplasmic virion morphogenesis and that certain UL20p domains that function in gB-syn3 virus-induced cell fusion are distinct from those functioning in gKsyn1 virus-induced cell fusion.